Determinación de las principales enfermedades del arroz (Oryza Sativa L.) y grado de incidencia en la zona de Montalvo - Mera Pinargote, José Leovigildo (2017)
VIII. SUMMARY The present research work was carried out in the grounds of Mrs. Delia Meléndez de Sigtu, located in the Babahoyo - Montalvo, Hada road. La Esperanza, Rcto. Los Beldacos, Canton Montalvo. The geographical coordinates are 790 39 'west longitude and 010 78' south latitude and 12 msnm. Seeds of the variety INIAP 14 and INIAP 15 were used as seed material. The treatments constituted by rice varieties and sub-treatments were studied with each treatment with untreated seed; treated seed (Vitavax); untreated seed + foliar application of fungicides and treated seed (Vitavax) + foliar application of fungicides. The experimental design of divided Plots was used, with two treatments, four sub-treatments and three replications. Tukey's test at 95% probability was used for the comparison of treatments and sub-treatments. For the good development of the plantation, soil preparation, seeding, irrigation, weed control, fertilization, phytosanitary control and harvesting were carried out. To evaluate the effects of treatments and sub-treatments data were taken in the field and laboratory. Field data were incidence and severity of diseases, fungicide efficacy, plant height, number of tillers, panicles at harvest, panicle length, panicle grains, 1000 grain weight, grain yield and economic analysis. The laboratory data were sample collection and processing, development, observation and identification of the causative agent, in vitro observations, identification of the causative agent. From the results obtained in the present experimental work, it was determined that at 60 and 75 days after transplant, treatments that did not use fungicides reported a higher incidence of diseases, being more susceptible the variety of rice Iniap 15 for R. solani, S. oryzae And P. oryzae and the Iniap 14 variety for H. oryzae; In the percentage of severity, at 60 and 75 days after transplantation, treatments that were untreated seed reached higher averages, being the Iniap 15 rice variety for R. solani, S. oryzae and Iniap 14 for H. oryzae and P. oryzae; The highest efficacy of the fungicides was due to the disease caused by Sarocladium with 82.3%; The variables plant height, panicle length, number of tillers and panicles / m2, grains per panicle and weight of 1000 grains reported higher averages in the Iniap 15 variety when the seed was treated (Vitavax) + foliar application of fungicides and the higher yield of the grain And profitable net profit was obtained by sowing the Iniap 14 variety, when the treated seed (Vitavax) + foliar application of fungicides was applied with a profit of $ 283.59.